Inexpensive gauge well for hydrological monitoring at remote multiple sites in watershed management projects - Yadav, R C; Bhushan, L S (Journal of Agricultural Engineering, 2006)
An inexpensive gauge well was designed for hydrological monitoring. The gauge well comprised a pipe stand of internal diameter 230 mm with wall thickness of 35 rom and length as per the convenience, usually 2000 mm. A box with locking arrangement was mounted at the top of the stand pipe to house the stage level recorder. The box can be removed for safe keeping and refixing during the next season.